PENERAPAN APLIKASI BERBASIS CLOUD UNTUK MENINGKATKAN EFISIENSI SISTEM PENJUALAN YUAN CAR SERVICE - Purnama Sari, Ratna; Astuti Isti Indriani; Zidni Husnia Fachrunnisa; Yennisa; Lulu Amalia Nusron; Anandita Zulia Putri; Vidya Vitta Adhivinna (Jurnal Berdaya Mandiri, 2025)
The purpose of this community service activity is to help Yuan Car Service in overcoming the problem of recording sales transactions that are still done manually, through the implementation of a digital-based accounting information system using the Kledo application. Previously, the sales business process at Yuan Car Service often experienced obstacles such as errors in inputting the price of goods, inaccuracy in calculating the total transaction, and delays in determining the Cost of Goods Sold (COGS). With the implementation of the Kledo system, the recording process becomes more efficient, accurate, and integrated with inventory data. This makes it easier for business owners to monitor financial conditions and stock in real-time, so that business decisions can be made quickly and accurately. Keywords : efficiency, information system, Kledo, SMEs.